1988
DOI: 10.1007/bf01457256
|View full text |Cite
|
Sign up to set email alerts
|

Torsional potential and strain energy distribution in an extended chain under stress

Abstract: Torsional potential V(~0) for the single bond transformation in an extended hexadecane, subjected to elongation, has been determined by molecular mechanics calculations. The stored elastic energy significantly modifies the potential V(~0), the conformational energies and the barriers of transition. Apart from the "soft" torsional coordinate, elastic energy is also dissipated considerably by bond stretching and angle bending. Maximal variations of the valence coordinates occur in the vicinity of the torsional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The change of the "hard" parameters, r i and h i , with deformation is especially notable within conformational defects or in their close vicinity. [15] As an illustration, typical changes in the valence geometry at the first (g + ) bond in kink defects can be mentioned. By stretching of a molecule to a critical strain the length of this CC bond changes from 153.7 pm to 155.2 pm and the corresponding CCC bond angle from 113.8 8 to 116.4 8.…”
Section: Defectmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of the "hard" parameters, r i and h i , with deformation is especially notable within conformational defects or in their close vicinity. [15] As an illustration, typical changes in the valence geometry at the first (g + ) bond in kink defects can be mentioned. By stretching of a molecule to a critical strain the length of this CC bond changes from 153.7 pm to 155.2 pm and the corresponding CCC bond angle from 113.8 8 to 116.4 8.…”
Section: Defectmentioning
confidence: 99%
“…The distribution of the stored energy along the PM molecules enables the location of the weak points most vulnerable to a bond breaking by tensile loading. [15] The related results were recently presented for a molecule involving a knot formed by adding an appropriate set of gauche defects to a PM chain. [16] It was found that the large amount of stored energy is located on the bonds at the entrance and exits points of the knot.…”
Section: Defectmentioning
confidence: 99%
“…(2) The deformation energy stored in the chain of the CG model should be passed to the atomistic level. In an atomistic molecular mechanics model 20,21 of a deformed chain, three types of valence coordinates (bond length r i , bending angle a i and torsional angle j i ) deviate from the equilibrium values and the deformation energy stored in the chain is dissipated in them. These deformations have been recorded in the CG structure during the nonequilibrium process, and a proper backmapping method should be able to translate these CG coordinates into atomistic ones.…”
Section: Introductionmentioning
confidence: 99%